HUSH, a Link Between Intrinsic Immunity and HIV Latency - Chougui, Ghina; Margottin-Goguet, Florence (Frontiers in Microbiology, 2019)
A prominent obstacle to HIV eradication in seropositive individuals is the viral persistence in latent reservoir cells, which constitute an HIV sanctuary out of reach of highly active antiretroviral therapies. Thus, the study of molecular mechanisms governing latency is a very active field that aims at providing solutions to face the reservoirs issue. Since the past 15 years, another major field in HIV biology focused on the discovery and study of restriction factors that shape intrinsic immunity, while engaging in a molecular battle against HIV. Some of these restrictions factors act at early stages of the virus life cycle, alike SAMHD1 antagonized by the viral protein Vpx, while others are late actors. Until recently, no such factor was identified in the nucleus and found active at the level of provirus expression, a crucial step where latency may take place. Today, two studies highlight HUSH as a potential restriction factor that controls viral expression and is antagonized by Vpx. This Review discusses HUSH restriction in the light of the actual knowledge of intrinsic immunity and HIV latency.